(untitled) ("Journal "U". Economy. Management. Finance.", 2024)
The article discusses the basic concepts of personnel security and the formation of personnel, highlights the threats of personnel activities in the civil service. Based on the analysis of the theoretical base and official recommendations of state bodies, the most important areas of activity for the issue of personnel security are identified to form an effective and reliable staff in public administration bodies.